2016
DOI: 10.1080/19371918.2015.1137510
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Social Work Students' Abortion Knowledge and Attitudes: Implications for Education and Research

Abstract: Researchers have established that individuals' abortion knowledge is positively associated with their support of abortion rights. However, social workers' personal beliefs regarding abortion are under-researched, even though social workers are often employed in health promotion and education roles in which the topic of abortion is encountered. The current study examines the results of a nationwide survey of social work students (N = 504) and explores the relationship between social work students' abortion know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…However, recent research shows that education about reproductive health is currently not often prioritized in social work educational curricula. For example, one study found that the vast majority of surveyed social workers reported that abortion was never or rarely discussed as part of their classroom education or field placement training; this echoes earlier findings that social work students lag with respect to abortion knowledge (Begun, Bird, Ramseyer Winter, Massey Combs, & McKay, 2016;Begun, Kattari, McKay, Ramseyer Winter & O'Neill, 2017;Ely, Flaherty, Akers, & Noland, 2012). Application of a TIC framework for social work education must therefore start with connecting social work principles to basic knowledge regarding sexual and reproductive health.…”
Section: Tic Social Work Frameworkmentioning
confidence: 65%
“…However, recent research shows that education about reproductive health is currently not often prioritized in social work educational curricula. For example, one study found that the vast majority of surveyed social workers reported that abortion was never or rarely discussed as part of their classroom education or field placement training; this echoes earlier findings that social work students lag with respect to abortion knowledge (Begun, Bird, Ramseyer Winter, Massey Combs, & McKay, 2016;Begun, Kattari, McKay, Ramseyer Winter & O'Neill, 2017;Ely, Flaherty, Akers, & Noland, 2012). Application of a TIC framework for social work education must therefore start with connecting social work principles to basic knowledge regarding sexual and reproductive health.…”
Section: Tic Social Work Frameworkmentioning
confidence: 65%
“…The journal Social Work published two of these articles ( n = 2) and the journal Social Work in Public Health one ( n = 1). Social work students were the sample for the quantitative article (Begun, Bird, Ramseyer Winter, Massey Combs, & McKay, 2016). The literature review investigated the presence of reproductive health topics in the social work literature (Wright et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The timely need for assessment and referrals by nonmedical practitioners, such as social workers and other behavioral health professionals, who interact with clients requesting information or referrals for reproductive health services on the front lines, in settings that are not necessarily related to reproductive health, is also critical. Given that in one study, 49% of social work students perceived an inability to provide referrals for abortion services (Ely, Flaherty, Akers, & Noland, 2012), and in another study 22% of social work students reported antichoice abortion stances (Begun, Bird, Winter, Combs, & McKay, 2016), it is essential that frontline practitioners in all settings prepare for potential reproductive health requests, and make a plan for how they will refer patients for abortion, even in cases where the requests are not expected in the existing setting. This is critical for promoting unintended pregnancy prevention, providing adequate prenatal care for those seeking to continue a pregnancy, and facilitating early, less costly access to abortion for those who choose to terminate but who may already be striving to overcome barriers to abortion, which can include IPV.…”
Section: Discussionmentioning
confidence: 99%